2020
DOI: 10.15421/022045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cameraria ohridella on accumulation of proteins, peroxidase activity and composition in Aesculus hippocastanum leaves

Abstract: This study analyzed the dynamics of leaf damage, the content of easily soluble proteins, benzidine-peroxidase activity and the composition of acid enzyme isoforms in the leaves of Aesculus hippocastanum L. under the influence of the chestnut miner Cameraria ohridella Deschka et Dimić (Lepidoptera, Gracillariidae) in plantations in one of the Ukraine’s largest industrial cities Dnipro, located in the steppe zone of Ukraine. During July-August, the destruction of leaves by the pest in relatively stable horse che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(18 reference statements)
1
2
0
2
Order By: Relevance
“…Peroxidase activation in cells of the black locust plant under the pest influence can be either the result of its involving in antioxidant protection or a non-specific response to stress associated with strengthening cell walls via the formation of lignins and oxidative phenols (Takashima et al, 2013;Zhao et al, 2016;Khromykh et al, 2018). The results obtained on the high activity of GPx in places of leaf damages by pest insects were confirmed with a number of studies (Singh et al, 2013;Seliutina et al, 2020).…”
Section: а вsupporting
confidence: 52%
“…Peroxidase activation in cells of the black locust plant under the pest influence can be either the result of its involving in antioxidant protection or a non-specific response to stress associated with strengthening cell walls via the formation of lignins and oxidative phenols (Takashima et al, 2013;Zhao et al, 2016;Khromykh et al, 2018). The results obtained on the high activity of GPx in places of leaf damages by pest insects were confirmed with a number of studies (Singh et al, 2013;Seliutina et al, 2020).…”
Section: а вsupporting
confidence: 52%
“…Changes in the qualitative and quantitative composition of secondary metabolites in horse chestnut leaves that have been infested with a leafminer provide plant resistance to the pest. Thus, a change in the activity of individual benzidine-peroxidase isomers contributes to maintaining the functional integrity of the photosynthetic system in chestnut leaves [52]. It is the inhibition of photosynthetic activity (decrease in the quantum efficiency of photosystem II) that provides violations of the coherence of the reactions of the Calvin cycle, which were recorded in infected leaves both on the illuminated and shaded sides of the crown of horse chestnut trees [53].…”
Section: Discussionmentioning
confidence: 99%
“…The functional state of trees may also be compromised by tree insects. Horse chestnut leaf miners, for instance, have resulted in a 2.1-fold increase in cytoplasmic peroxidase activity (Seliutina et al 2020). Miller (1997) found that twigs weakened by ovipositional wound damage in urban forests due to cicadas are more likely to die later in the summer and break during windstorms, littering the ground.…”
Section: Narrative Synthesismentioning
confidence: 99%